Inequality in health service utilization among migrant and local children: a cross-sectional survey of children aged 0-14 years in Shenzhen, China - Xiatong Ke; Liang Zhang; Zhong Li; Wenxi Tang (BMC, 2020)
Abstract Background Shenzhen is characterized with the largest scale of migrant children among all the cities in China. Unequal access to health services among migrant and local children greatly affects health equity and has a profound impact on the quality of human capital. This study aimed to investigate differences in using community-based healthcare between local and migrant children and to identify the influencing factors in Futian District of Shenzhen. Methods Households in 12 communities in Futian District of Shenzhen were randomly sampled. Children aged 0-14 years were investigated using self-administered questionnaire - the 2018 Survey of Health Service Needs of Chinese Residents. Differences in healthcare including physical examination, feeding guidance, development guidance, disease prevention guidance, injury prevention guidance, oral health guidance, and mental health guidance, were tested between local and migrant children. Binary logistic regressions were used in identifying potential influencing factors which affected the use in the above healthcare items. Results A total of 936 participants from1512 families were sampled and 508 of them were included. Compared with local children, migrant children had less use of development guidance (OR = 0.417, 95% CI: 0.279-0.624) and oral health care guidance (OR = 0.557, 95% CI: 0.381-0.813). Children whose father received higher education level enjoyed a better use of disease prevention guidance as compared to whose father stopped at junior high school education or below (senior high vs junior high and below, OR = 1.286, 95% CI: 0.791-2.090; bachelor and above vs junior high and below, OR = 2.257, 95% CI: 1.417-3.595). Children whose fathers were blue-collar workers had less use of injury prevention guidance (OR = 0.750, 95% CI: 0.334-1.684) and mental health guidance (OR = 0.784, 95% CI: 0.295-2.080) as compared to whose father were white collar workers. Conclusions Except feeding guidance, healthcare utilization were lower among migrant children than among local children. Generally, fathers have a stronger influence on children's use of community-based healthcare than mothers do. The potential influence of fathers in promoting children's healthcare use behaviors should be carefully considered, and fathers' attention to children's health should be increased.